Usefulness of the waist-to-height ratio for predicting cardiometabolic risk in children and its suggested boundary values. Issue 2 (February 2022) - Muñoz-Hernando, Judit; Escribano, Joaquin; Ferré, Natalia; Closa-Monasterolo, Ricardo; Grote, Veit; Koletzko, Berthold; Gruszfeld, Dariusz; ReDionigi, Alice; Verduci, Elvira; Xhonneux, Annick; Luque, Veronica
Summary: Background & aims: Only limited information is available on the usefulness of the waist-to-height ratio (WHtR) as an abdominal obesity marker in children. Our aim was to compare the ability of a WHtR >90th percentile, a WHtR ≥0.50, a WHtR ≥0.55 and a BMI z-score ≥2 SD to predict cardiometabolic risk in children followed-up at different ages. Methods: We evaluated data from 660 children at 5, 8 and 11 years of age who participated in the Childhood Obesity Project trial in 5 European countries. We classified children with or without cardiometabolic (CMet) risk (yes vs. no) according to the presence of ≥ 2 parameters (blood pressure, HOMA-IR, triglyceride levels and high-density lipoprotein (HDL) cholesterol levels) ≥90th percentile. Results: The odds ratio for CMet risk in children at all followed-up ages was statistically significant for all measures. The OR for the WHtR≥0.55 cut-off was 29.1 (5.6, 151.7) at 5 years of age, 11.8 (4.1, 33.8) at 8 year of age and 3.6 (1.7, 7.7) at 11 years of age, compared to the WHtR<0.55 cut-off. The WHtR≥0.55 cut-off showed a higher OR at younger ages than the BMI z-score ≥2SD, WHtR ≥90th percentile and WHtR≥0.50 cut-offs and a higher positive predictive value (82% at 5 years of age compared to 55%, 36% and 41%, respectively). Conclusion: A WHtR≥0.55 is a suitable cut-off for screening children at high cardiometabolic risk in the general young European population.